CHALLENGES AND REGENERATION STRATEGIES OF TURONGGO YAKSO MUDO TRADITIONAL ARTS AT SDN 2 SUMBEREJO - Gerry Ironika (Universitas Islam Balitar, 2024)
This study focused on identifying challenges and formulating strategies needed for the regeneration of Turonggo Yakso Mudo traditional art at SDN 2 Sumberejo. Turonggo Yakso Mudo art was one of the cultural heritages that not only has aesthetic value, but also functions as a medium to maintain local cultural identity and strengthen social ties in Sumberejo Village. However, this art faced various significant challenges in the modern era, including the declining interest of the younger generation in traditional arts and decreasing support from the local community. This study used a qualitative descriptive research, with data collection methods through direct observation, in-depth interviews with teachers and artists at SDN 2 Sumberejo, and analysis of relevant documentation. The results of the study indicated that the main challenges in the regeneration of Turonggo Yakso Mudo art included the low enthusiasm of the younger generation, limited resources for practice and performances, and the negative impact of the COVID-19 pandemic which has significantly hampered cultural activities. These challenges was further exacerbated by modernization that shifts people's entertainment preferences towards a more global and digital direction. However, this study also found that there was several effective strategies that can be applied to face these challenges. These strategies included improving cultural education through school curriculum, actively involving communities in arts activities, and using technology and social media to expand the reach of promotion and attract the interest of the younger generation in this traditional art. With the implementation of the right strategy, it is hoped that Turonggo Yakso Mudo art can e continued to live and develop even in the midst of changing times. Based on the results of the study, it can be concluded that the regeneration of Turonggo Yakso Mudo art at SDN 2 Sumberejo requires close cooperation between schools, communities, and government. Only with good synergy and a comprehensive approach could the sustainability of this cultural tradition be guaranteed and passed on to the next generation.